EFFECT OF CULTURAL PRACTICES ON THE INCIDENCE AND NATURAL CONTROL OF Rupela albinella IN TWO VARIETIES OF RICE AND ITS RELATION TO YIELDS - CARDONA, CÉSAR; GONZÁLEZ, JOAQUÍN (Revista Colombiana de Entomología, 1979)
The effect of spacing and nitrogen fertilization on the population levels and natural control of Rupela albinella (Cramer) was studied on two rice varieties: CICA 8 and IR-22. CICA 8 was more susceptible to the borer; percentage infestation was higher when the rice was transplanted at 30 x 30 cm than at 20 x 20 cm. Nitrogen fertilization at 0,80 y 160 kg/ha did not have a significant effect un infestation. There was not a significant correlation between the percentage of damaged stems and yields. Larval parasitism by Strabotes abdominalis obscurus Zwart and Trathala sp. (Hymenoptera: Ichneumonidae) ranged from 64 to 71% but was not influenced by any of the cultural practices studied, the ge' neral conclusion is that chemical control of this borer is not justified.